1998
DOI: 10.1073/pnas.95.26.15223
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Hsp70 molecular chaperone, DnaK, with its cochaperone DnaJ

Abstract: Chaperones of the Hsp70 family bind to unfolded or partially folded polypeptides to facilitate many cellular processes. ATP hydrolysis and substrate binding, the two key molecular activities of this chaperone, are modulated by the cochaperone DnaJ. By using both genetic and biochemical approaches, we provide evidence that DnaJ binds to at least two sites on the Escherichia coli Hsp70 family member DnaK: under the ATPase domain in a cleft between its two subdomains and at or near the pocket of substrate binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
314
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(343 citation statements)
references
References 29 publications
(32 reference statements)
25
314
0
3
Order By: Relevance
“…The first interaction, which has been recognized for many years, seems to occur between the N-terminal J-domain of DnaJ and the Nterminal ATPase domain of DnaK. The second interaction site was proposed to be between an unidentified site in DnaJ and the C-terminal substrate binding site in DnaK (35). It appears that we have succeeded in identifying that this required additional interaction site in class I DnaJ homologues is mediated by the highly conserved zinc center II.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The first interaction, which has been recognized for many years, seems to occur between the N-terminal J-domain of DnaJ and the Nterminal ATPase domain of DnaK. The second interaction site was proposed to be between an unidentified site in DnaJ and the C-terminal substrate binding site in DnaK (35). It appears that we have succeeded in identifying that this required additional interaction site in class I DnaJ homologues is mediated by the highly conserved zinc center II.…”
Section: Discussionmentioning
confidence: 90%
“…7). The requirement for such additional interactions between DnaJ and DnaK-substrate protein complexes have been suggested before in DnaK suppressor studies that showed that DnaJ binds to at least two sites in DnaK (35). The first interaction, which has been recognized for many years, seems to occur between the N-terminal J-domain of DnaJ and the Nterminal ATPase domain of DnaK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, single point mutations of the linker and hydrophobic cleft residues perturb the NBD ATPase activity and disturb its regulation by the SBD and cochaperones (2,16,32,33). The fact that the hydrophobic cleft is the binding site for the Hsp70 cochaperone DnaJ, which regulates the rate of ATP hydrolysis (2,34,35), indicates that cochaperone regulation of ATPase activity most likely occurs through the same allosteric networks (i.e., via the linker and the hydrophobic cleft). Intriguingly, the hydrophobic cleft comprises a sector of coevolved residues in the NBD, which is important for stabilizing the interdomain interfaces and mediating allosteric communication between the NBD and SBD (36).…”
Section: Discussionmentioning
confidence: 99%
“…The following proteins were purified essentially as described: RNA polymerase (38), His-tagged 32 (18), GroEL, GroES (39), DnaK, DnaJ, and GrpE (40). Misfolded proteins were removed from chaperone preparations as described (16).…”
Section: Methodsmentioning
confidence: 99%